Evaluation and comparison of hamstring extensibility in young paddlers - P.A. López-Miñarro; F. Alacid; C. Ferragut; A. García (Asociación Española de Ciencias del Deporte, 2010)
Hamstring extensibility was measured in 63 infantil paddlers (mean age: 13.35 ± 0.59 years) of three groups (23 male kayak (HK), 22 females kayak (DK) and 20 male canoe (HC)) using the straight leg raise test (SLR), sit-and-reach score and lumbo-pelvic position in maximal reaching of the sit-and-reach test maintaining the knees extended. Mean values of the SLR were 85.45º ± 11.78º (DK), 73.96º ± 6.40º (HK) and 71.70º ± 9.77º (HC) for left limb and 87.09º ± 12.55º, 74.52º ± 4.81º y 70.55º ± 9.78º for right limb, respectively. Significant differences were found between DK with respect to male groups in both legs. The frequency of reduced hamstring extensibility was high in males (23%-27% DK; 43%-48% HK; 70%-80% HC). There was a greater variability in males between reduced and normal hamstring extensibility (20.0%-95.7% of normal values). In conclusion, we found a high frequency of reduced hamstring extensibility in young paddlers, especially in canoeists. Key Words: hamstring muscle, extensibility, paddlers, testing.